EKRANISASI CERITA NOVEL AYAH, MENGAPA AKU BERBEDA? KARYA AGNES DAVONAR DENGAN FILM AYAH, MENGAPA AKU BERBEDA? KARYA SUTRADARA FINDO PURWONO HW - Yeni Putri; Hasanuddin WS Hasanuddin WS; Zulfadhli Zulfadhli (Jurnal Bahasa dan Sastra, 2014)
The purpose of this article (a) to describe story of episode novel Ayah, Mengapa Aku Berbeda?created by Agnes Davonar, (b) to describe story of episode film Ayah, Mengapa Aku Berbeda?director by Findo Purwono Hw, (c) to describe the  comparison story of episode novel Ayah, Mengapa Aku Berbeda?created by Agnes Davonar with film Ayah, Mengapa Aku Berbeda?director by Findo Purwono Hw. The data of this article is the story of Episode novel Ayah, Mengapa aku Berbada? created by Agnes Davonar and film Ayah, Mengapa aku Berbeda? by the director Findo Purwono Hw. The analysis teqhnique used with ekranisasi theory. The findings of the study showed that the decrease story of episode novel Ayah, Mengapa Aku Berbeda?created by Agnes Davonar in film Ayah, Mengapa Aku Berbeda?director by Findo Purwono Hw become to 105 story of episode. Increase story of episode in film Mengapa Aku Berbeda?director by Findo Purwono Hw become to 41 story of episode. The same variation changes event, figure and background story of episode in novel Ayah, Mengapa Aku Berbeda?created by Agnes Davonar and film Ayah, Mengapa Aku Berbeda?director by Findo Purwono Hw become to 32 story of episode.